Real‐world efficacy and safety of daclatasvir and asunaprevir therapy for hepatitis C virus‐infected cirrhosis patients. Issue 3 (March 2017) - Morio, Kei; Imamura, Michio; Kawakami, Yoshiiku; Morio, Reona; Kobayashi, Tomoki; Yokoyama, Satoe; Nagaoki, Yuko; Kawaoka, Tomokazu; Tsuge, Masataka; Hiramatsu, Akira; Makokha, Grace Naswa; Hayes, C Nelson; et al.
Abstract: Background and Aims: Daclatasvir and asunaprevir combination therapy has shown a high virological response for chronic genotype 1 hepatitis C virus (HCV) infected‐patients. However, the real‐world efficacy and safety of the therapy for patients with cirrhosis are unknown. Methods: A total of 252 patients with genotype 1 HCV infection (158 with chronic hepatitis and 94 with compensated liver cirrhosis) were treated with 24 weeks of daclatasvir and asunaprevir combination therapy. Plasma concentrations of daclatasvir and asunaprevir at day 5 of treatment, end‐of‐treatment response, sustained virological response (SVR), and the frequencies of adverse events were analyzed. Result: Plasma asunaprevir concentration was significantly higher, and daclatasvir concentration tended to be higher, in cirrhosis patients compared with chronic hepatitis patients. End‐of‐treatment response was achieved in 95.6% and 94.7% of chronic hepatitis and cirrhosis patients, respectively, and SVR was achieved in 94.3% and 92.6%. Although pre‐treatment NS5A drug resistant‐associated variants were detected, a high SVR rate was achieved when the population frequency of the variant was low. The frequencies of treatment‐related adverse events in cirrhosis patients were similar to those in chronic hepatitis patients. Treatment discontinuation due to adverse events occurred in three and two patients in chronic hepatitis and cirrhosis groups, respectively; however, four out of five patients with treatment discontinuation nonetheless achieved SVR. Conclusion: Patients with compensated liver cirrhosis have similar virological response and tolerance for daclatasvir plus asunaprevir therapy to patients with chronic hepatitis. This combination therapy might offer a safe and effective treatment for chronic HCV infected‐patients with compensated cirrhosis.